2014
DOI: 10.1186/1687-6180-2014-60
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of BER performance of nonlinearly amplified FBMC/OQAM and OFDM signals

Abstract: In this paper, we introduce an analytical study of the impact of high-power amplifier (HPA) nonlinear distortion (NLD) on the bit error rate (BER) of multicarrier techniques. Two schemes of multicarrier modulations are considered in this work: the classical orthogonal frequency division multiplexing (OFDM) and the filter bank-based multicarrier using offset quadrature amplitude modulation (FBMC/OQAM), including different HPA models. According to Bussgang's theorem, the in-band NLD is modeled as a complex gain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 20 publications
1
48
0
Order By: Relevance
“…Figure 4 shows the BER plots for two values of the IBO, IBO = 4 dB and IBO = 8 dB. From this figure, we can see that BER performance depends heavily on the HPA IBO, which is an expected result since there is a proportionality between the nonlinear noise variance and IBO as it was stated in [14].…”
Section: Simulationssupporting
confidence: 48%
See 1 more Smart Citation
“…Figure 4 shows the BER plots for two values of the IBO, IBO = 4 dB and IBO = 8 dB. From this figure, we can see that BER performance depends heavily on the HPA IBO, which is an expected result since there is a proportionality between the nonlinear noise variance and IBO as it was stated in [14].…”
Section: Simulationssupporting
confidence: 48%
“…The impact of NLD on OFDM signals was presented in [10,11] and a performance analysis of nonlinear OFDM and OFDM-MIMO systems was derived in [12,13]. As for FBMC systems, the authors in [14] carried out a theoretical analysis of BER performance for nonlinearly amplified FBMC/OQAM signals under additive white Gaussian noise (AWGN) and Rayleigh fading channels. Similarly, [15] has recently derived a closedform expression for the BER of gray-coded M-ary (QAM or OQAM)-based OFDM in the presence of HPA NLD under a frequency flat fading Rayleigh channel.…”
Section: Introductionmentioning
confidence: 99%
“…This theory states that the output of the non linear HPA circuit is a function of the linear scale parameter ζ of the input signal and a non linear distortion ς uncorrelated with the input signal and modeled as a complex Gaussian random variable ς CN (0, σ 2 ς ). According to [33], [44], the parameters ζ and σ 2 ς for SEL are given by [45,Eq. (17)]…”
Section: B Non Linear Hpa Models Analysismentioning
confidence: 99%
“…Due to OQAM, the OQAM demodulated FBMC received constellation does not suffer from this rotation but the phase distortion of (22) creates an additional amplitude spreading on demodulated QAM symbols. This phenomenon can be explained following the reasoning provided in [33]. Simulations showed that the additional amplitude spread on QAM symbols caused by the phase distortion introduces a bigger MSE degradation than the phase rotation on the constellation of the other waveforms that do not use OQAM, and this at the same drive level of the PA.…”
Section: Performance Comparisonmentioning
confidence: 99%